Casual Associations and Shape Between Prepuberty Body Mass Index and Early Onset of Puberty: A Mendelian Randomization and Dose–Response Relationship Analysis - Fang, Jiao; Yuan, Jingyi; Zhang, Dandan; Liu, Wanxu; Su, Puyu; Wan, Yuhui; Zhang, Zhihua; Tao, Fangbiao; Sun, Ying (Frontiers in Endocrinology, 2022)
Abstract: Background: There is an ongoing controversial issue regarding whether onset of puberty is related to childhood-BMI. Objectives: This study aims to investigate causal association and its shape between prepuberty-BMI and early puberty onset. Methods: Breast development and testicular volume were assessed annually from population-based prospective cohort of 997 children for consecutive years by professional endocrinologists. Seventeen puberty- and BMI-related SNPs were selected to calculate polygenic risk score. Two-stage least squares method was used to assess and confirm causal effects. Dose-response association between prepuberty-BMI and early puberty onset were conducted by using restricted cubic splines Cox regression. Results: After adjusted for covariates, prepuberty-BMI was positively associated with early thelarche among girls (coefficients=0.18, 95%CI: 0.01, 0.29). Non-linear model suggested an inverted U-shaped relationship between prepuberty-BMI and risk for early thelarche (χ2=276.3, P<0.001). The risk for early thelarche increased rapidly from prepuberty-BMI at 15.70 kg/m2 (P25) to 20.75 kg/m2 (P85) and gradually decreased afterwards. Compared with the P25 of prepuberty-BMI, the HRs (95%CI) for early thelarche were 5.08 (1.15, 8.55), 4.48 (1.02, 7.74), 10.15 (3.93, 17.50) and 8.43 (1.91, 13.71) for percentiles P25-P50, P50-P75, P75-P85 and ≥ P85 of BMI categories, respectively. In boys, compared with the P25 of prepuberty-BMI, boys with BMI between P25-P50 showed an increased risk of early puberty (HR: 3.94, 95%CI: 1.44, 6.80). Conclusions: Prepuberty-BMI may serve the purpose of identifying the girls at higher risk of early thelarche, which could assist in adaptation of prevention and intervention strategies targeting childhood obesity. The findings emphasize a nonlinear correlation between prepuberty-BMI and early puberty onset.